Systematic Medication Review in General Practice by an Interdisciplinary Team: A thorough but Laborious Method to Address Polypharmacy among Elderly Patients - Dagmar Abelone Dalin; Charlotte Vermehren; Anette Kobberø Jensen; Janne Unkerskov; Jon Trærup Andersen (MDPI AG, 2020)
Polypharmacy increases the risk of hospitalization but may be reduced by medication review. The study objective is to describe and evaluate a method for conducting medication review in general practice by an interdisciplinary medication team of pharmacists and physicians-in this case conducted by a team from the Department of Clinical Pharmacology-based on information concerning medication, diagnosis, relevant laboratory data and medical history supplied by the general practitioner. We discussed the medication review with the patients' general practitioners and received feedback from them regarding acceptance rates of the recommended changes. Ninety-four patients with a total of 1471 prescriptions were included. A medication change was recommended for nearly half of the prescriptions (48%); at least one change of medication was recommended for all patients. The acceptance rate for recommended medication changes was 55%, corresponding to a mean of 4.2 accepted recommendations per patient. For 18% of all 1471 prescriptions, the general practitioner agreed either to discontinue (stop the medication completely) or reduce the dose of the medication. This method is thorough, but since it requires several healthcare professionals, it is rather time-consuming. There is a need to support medication review in general practice, but although this method may be too time consuming in most cases, it may nevertheless prove to be a useful tool managing the most complicated patients.